Effect of Saccharomyces cerevisiae Live Cells on In Vivo Digestibility and Nitrogen Excretion in Lactating Buffaloes - Masucci, Felicia; Uzun, Pinar; Grasso, Fernando; De Rosa, Giuseppe; Di Francia, Antonio (Journal of Buffalo Science, 2014)
The effects of dietary inclusion of Saccharomyces cerevisiae culture on intake, in vivo digestibility, and fecal nitrogen excretion were examined in dairy buffalo. Forty lactating buffalo cows were equally divided into Control and Saccharomyces groups, balanced for milk production, parity, and days in milk. Two subsequent 16-d experimental phases were carried out. For both groups during the first experimental period a TMR based on maize silage (maize-TMR) was used, whereas in the second period an alfalfa haylage (alfalfa-TMR) was administered to the animals. In each experimental period, Saccharomyces group was supplemented with 50 g/head/day of yeast (Biocell®, Limena, Padova, Italy), corresponding to 20×109 CFU/head/day Saccharomyces cerevisiae NCYC Sc47 strain. The yeast supplement was top-dressed onto the morning feed. Dry matter intake (DMI) was assessed for 6 consecutive d on group basis, by the difference between feed offered and refused. In the last 3 days of experimental period in vivo digestibility was determined by using acid-insoluble ash (AIA) as an intrinsic digestibility marker. Saccharomyces supplemented buffalo cows presented greater DMI of maize-TMR, whereas no statistical differences between the groups were observed for alfalfa-TMR. Saccharomyces supplementation significantly improved in vivo digestibility of both TMR. Fecal nitrogen excretion was significantly reduced by the use of yeast supplementation. Results suggest that the inclusion of Saccharomyces cerevisiae culture in the diet for lactating buffaloes can be recommended for its effects on cow’s digestive efficiency and fecal nitrogen excretion.